Visualizing and Quantifying In Vivo Cortical Cytoskeleton Structure and Dynamics - Rosero, Amparo; Oulehlová, Denisa; Žárský, Viktor; Cvrčková, Fatima (Methods in molecular biology (Clifton, N.J.), 2019)
The cortical microtubule and actin meshworks play a central role in the shaping of plant cells. Transgenic plants expressing fluorescent protein markers specifically tagging the two main cytoskeletal systems are available, allowing noninvasive in vivo studies. Advanced microscopy techniques, in particular confocal laser scanning microscopy (CLSM), spinning disk confocal microscopy (SDCM), and variable angle epifluorescence microscopy (VAEM), can be nowadays used for imaging the cortical cytoskeleton of living cells with unprecedented spatial and temporal resolution. With the aid of free computing tools based on the publicly available ImageJ software package, quantitative information can be extracted from microscopic images and video sequences, providing insight into both architecture and dynamics of the cortical cytoskeleton.
Keywords: Arabidopsis; konfokální mikroskopie; fluorescenční mikroskopie; Fluorescent proteins; Cytoskeleton; Image Processing, Computer-Assisted; Microtubules; Microscopy, Confocal; počítačové zpracování obrazu; rostlinné buňky; Image analysis; Microscopy, Fluorescence; SDCM; ImageJ; mikrotubuly; Plant Cells; cytoskelet; Actin; CLSM; VAEM